Extramedullary Hematopoiesis in Uterine Leiomyoma Associated with Numerous Intravascular Thrombi - Xiaoyan Cui; Deniz Peker; Heather O. Greer; Michael G. Conner; Lea Novak (Case Reports in Pathology)
We report a case of extramedullary hematopoiesis (EMH) in uterine leiomyoma and associated numerous intravascular thrombi. A 29-year-old nulliparous female presented with heavy vaginal bleeding and a hematocrit of 22%. No bone marrow biopsy has been performed. She had a history of uterine leiomyomata and menorrhagia for a year. A transvaginal ultrasound confirmed the presence of a uterine leiomyoma. The patient was treated conservatively with oral contraceptive pills due to desire for fertility. However, she continued to have heavy vaginal bleeding and developed bilateral upper extremity deep vein thrombosis and multiple superficial vein thromboses after two months. An exploratory laparotomy with uterine myomectomy was performed. Gross examination of the specimen revealed a single nodular mass measuring 10.0×9.5×7.5 cm with a white-tan swirling cut surface. Microscopic examination revealed benign smooth muscle consistent with leiomyoma and numerous intravascular thrombi both with areas of EMH. Immunohistochemical stains confirmed the presence of all three benign lineages of hematopoietic cells. Occurrence of EMH in uterine leiomyoma and intravascular thrombi is very rare. It may be related to systemic hematopoietic stimulation due to severe chronic anemia and local presence of hematopoietic growth factors and/or cytokines.